Strategic Opportunities Aspect of CSR for Improving Location Advantages in Developed and Emerging Markets (2022)
This case study examines how a Japanese company uses CSR and ESG activities to incorporate a new global expansion strategy and strengthen its stakeholders’ relations in different locations around the world. The author uses a case study method with a single setting, and multiple units of analysis and pattern matching among 39 regions and countries, divided into home and host countries. The host countries are additionally divided into ‘developed’, ‘emerging’, and ‘least developed’. This study contributes to the extant literature by showing that both developed and emerging markets create strategic assets for the company. It also proved MNE’s stakeholders in emerging and developed markets determined the CSR practices because many developed countries need CSR activities to support vulnerable groups within their societies. This study explores the under-researched area of MNEs’ CSR activities regarding poverty and development in least-developed countries.